A multi-disciplinary approach to the study of an assemblage of copper-based finds assigned to the prehistory and proto-history of Fucino, Abruzzo, Italy - Mascelloni M.L.; Cerichelli G.; Ridolfi S. (Journal of Mining and Metallurgy. Section B: Metallurgy)
The project aims to characterize, through a body of archaeometric analyses, an assemblage of copperbased finds known as 'Fucino bronzes', most of which lack any finding data. The Fucino bronzes include artefacts that emerged during the drainage of Lake Fucino at the end of the XIX century, as well as bronzes acquired locally or dug out later by several collectors on behalf of the various Italian museums where finds are currently distributed. Our work explores the dynamics related to the objects assembled and relationships between production centres, local workshops, and the emergence of iron. This study proceeds concurrently with the following research and cataloguing procedures: quantification, portable ED-XRF analysis, metallography, and the development of a database. The finds are grouped into three main categories: ornaments and accessories, instruments, and weapons. The quantification is also classed in terms of typology, technology, chronology, and territory whenever possible, in order to establish customized models for the interpretation of data. Metallographic analysis is carried out using optical microscope (OM) and SEM. On this occasion we report the results of selected materials, such as 'Kardiophylakes' that make up about one-third of the known samples in the assemblage, thirty eight of which have a reported provenance from specific Fucino sites.